Assessing biomass steam gasification technologies using a multi-purpose model. (1st December 2016) - Sepe, Angelo Maria; Li, Jun; Paul, Manosh C.
Highlights: Comprehensive study on biomass steam gasification technologies is carried out. Gasification performance at varying conditions is studied by a robust multi-phase numerical model. Solar-assisted gasification produces high quality syngas. Modelling prediction corroborates with experimental and other data in literature. Abstract: Two advanced steam-gasification technologies of biomass, high temperature steam gasification (HTSG) and solar-assisted steam gasification, have been thermodynamically investigated in this work and compared with both conventional auto-thermal gasification and High Temperature Air and Steam Gasification (HTAG). A multi-phase, multi-physics 1D steady-state model has been built up to predict the biomass gasification performance, efficiency, yield and species of produced syngas at varying gasification methods and input parameters. In particular, heterogeneous and homogenous gasification reactions coupled with a radiative transfer were employed in the solar-assisted steam gasification. The results showed that the solar-assisted steam gasification technology demonstrates its potential to produce high quality syngas (nearly 42% H2 and 35% CO). Moreover, it upgrades the heating value of the product syngas up to 1.4 times more than the original value, due to the additional solar energy induction. Compared with conventional auto-thermal gasification, it was found that the process efficiency can be improved from 65% to 81% if using the HTAG technology and the content of hydrogen in the syngas increased from 30% to 55% if applying HTSG. The modelling results agree considerably with the reported experimental and modelling data in literature, and also able to return a direct comparison of advantage and disadvantage of each gasification method, in terms of syngas quantity and quality.